The complete mitogenome of the endangered freshwater crayfish Cherax tenuimanus (Smith 1912) (Crustacea: Decapoda: Parastacidae). (1st November 2016) - Austin, Christopher M.; Tan, Mun Hua; Gan, Huan You; Gan, Han Ming
Abstract: Next-Gen sequencing was used to recover the complete mitochondrial genome of Cherax tenuimanus . The mitogenome consists of 15, 797 base pairs (68.14% A + T content) containing 13 protein-coding genes, two ribosomal subunit genes, 22 transfer RNAs, and a 779 bp non-coding AT-rich region. Mitogenomes have now been recovered for all six species of Cherax native to Western Australia.